Fabrication and characterization of (1-x)BiFeO3-xBaTiO3 ceramics prepared by a solid state reaction method - Chandarak S. (2014)
In this study, BiFeO3-BaTiO3 ceramics have been fabricated by a solid-state reaction method. The effects of BaTiO3 content in the (1-x)BiFeO3-xBaTiO3 (x = 0.1, 0.2, 0.25, 0.3, 0.4, 0.5) system on crystal structure and magnetic, dielectric, and ferroelectric properties were investigated. Perovskite BiFeO3 was stabilized through the formation of a solid solution with BaTiO3. Rhombohedrally distorted structure (1-x)BiFeO3-xBaTiO3 ceramics showed strong ferromagnetism at x = 0.5. Dielectric and ferroelectric properties of the BiFeO3-BaTiO3 system also changed significantly upon addition of BaTiO3. It was found that the maximum dielectric and ferroelectric properties were exhibited in the (1-x)BiFeO3-xBaTiO3 system at x = 0.25. This suggested the morphotropic phase boundary (MPB) with the coexistence of both rhombohedral and cubic phases of the (1-x)BiFeO3-xBaTiO3 system at x = 0.25. © 2009 Journal of Magnetics.